CD38-specific nanobodies allow in vivo imaging of multiple myeloma under daratumumab therapy - Pape, Luca Julius; Hambach, Julia; Gebhardt, Anna Josephine; Rissiek, Björn; Stähler, Tobias; Tode, Natalie; Khan, Cerusch; Weisel, Katja; Adam, Gerhard; Koch-Nolte, Friedrich; Bannas, Peter (Frontiers in Immunology, 2022)
Rationale: Recent studies have demonstrated the feasibility of CD38-specific antibody constructs for in vivo imaging of multiple myeloma. However, detecting multiple myeloma in daratumumab-pretreated patients remains difficult due to overlapping binding epitopes of the CD38-specific imaging antibody constructs and daratumumab. Therefore, the development of an alternative antibody construct targeting an epitope of CD38 distinct from that of daratumumab is needed. We report the generation of a fluorochrome-conjugated nanobody recognizing such an epitope of CD38 to detect myeloma cells under daratumumab therapy in vitro, ex vivo, and in vivo. Methods: We conjugated the CD38-specific nanobody JK36 to the near-infrared fluorescent dye Alexa Fluor 680. The capacity of JK36AF680 to bind and detect CD38-expressing cells pretreated with daratumumab was evaluated on CD38-expressing tumor cell lines in vitro, on primary myeloma cells from human bone marrow biopsies ex vivo, and in a mouse tumor model in vivo. Results: Fluorochrome-labeled nanobody JK36AF680 showed specific binding to CD38-expressing myeloma cells pretreated with daratumumab in vitro and ex vivo and allowed for specific imaging of CD38-expressing xenografts in daratumumab-pretreated mice in vivo. Conclusions: Our study demonstrates that a nanobody recognizing a distinct, non-overlapping epitope of CD38 allows the specific detection of myeloma cells under daratumumab therapy in vitro, ex vivo, and in vivo.